Emotional labor of in-home caregivers of the elderly (Research, Society and Development, 2020)
This qualitative study aimed to understand the nature of the emotional labor of in-home caregivers of the elderly in a city in the state of Minas Gerais. For this, ten interviews were conducted with professionals in this field, where it was possible to perceive an extremely exhausting and precarious work reality. This reality seems to have implications on both the physical and mental health of the caregiver, causing him depression and stress. The interviewees reported to have some financial dependence on the activity. They use an emotional work that makes them able to support their tasks and even the day to day. In this sense, reports of self-annulment are frequent, where the subject makes his own suffering invisible to the detriment of the patient. Such strategy, which generates emotional dissonance, makes caregivers need to play two distinct work roles.